ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU DENGAN METODE ECONOMIC ORDER QUANTITY (EOQ) PADA USAHA MIE SINAR SULAWESI CAP DUA ANGSA GUNA PENINGKATAN EFISIENSI BIAYA PERSEDIAAN - Yogi Elsandi (Jurnal Administrasi Bisnis Fisipol Unmul, 2019)
Nowadays economy has developed very fast, along with the rapid development of science and technology which is increasingly modern makes the competition between companies become more intense. With the intense competition between companies encouraging each company to do a good inventory control in supporting and expediting the production activities. According to Assauri (2008:176) Inventory control is one of the activities of the activities sequence that are closely related to each other in the entire company's production operations in accordance with what has been planned both time, quantity, quality, and cost. In an effort to control inventory one of the methods that can be used is the "Economic Order Quality” (EOQ) analysis. EOQ is the most economical volume or amount of purchases to be made at each time of purchase. In addition to determining EOQ, companies also need to determine the point of order for raw materials to be used or reorder point (ROP) and determine the amount of safety stock. Data sourced from Mie Sinar Sulawesi Cap Dua Angsa Company. It can be seen the results of research conducted show that the difference in quantity and frequency of purchases that are more efficient with a total quantity of 10.910 kg in one order and frequency of 5 orders and reorder point is 2.212 kg while the amount of safety stock is 1.892 kg. By applying the EOQ method, it can make a company able to create economical inventory costs. However, before implementing this method the company must also calculate the important aspects such as capacity, warehouse, capital costs, and the risks of damage that the company must avoid.